2014
DOI: 10.1063/1.4866356
|View full text |Cite
|
Sign up to set email alerts
|

Dramatically enhanced self-assembly of GeSi quantum dots with superior photoluminescence induced by the substrate misorientation

Abstract: A dramatically enhanced self-assembly of GeSi quantum dots (QDs) is disclosed on slightly miscut Si (001) substrates, leading to extremely dense QDs and even a growth mode transition. The inherent mechanism is addressed in combination of the thermodynamics and the growth kinetics both affected by steps on the vicinal surface. Moreover, temperature-dependent photoluminescence spectra from dense GeSi QDs on the miscut substrate demonstrate a rather strong peak persistent up to 300 K, which is attributed to the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
(24 reference statements)
2
9
0
Order By: Relevance
“…It has been found that surface energy is considerably influenced by the miscut angles. 21,31,41 The overall fact that the NW width is nearly not affected by the miscut angle indicates that the variation in surface energy is balanced by that in elastic energy due to the anisotropicity of the vicinal surface. Our results disclose that the elastic energy on the vicinal surface is also considerably affected by the miscut angle.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been found that surface energy is considerably influenced by the miscut angles. 21,31,41 The overall fact that the NW width is nearly not affected by the miscut angle indicates that the variation in surface energy is balanced by that in elastic energy due to the anisotropicity of the vicinal surface. Our results disclose that the elastic energy on the vicinal surface is also considerably affected by the miscut angle.…”
Section: Resultsmentioning
confidence: 99%
“…These are the main factors underlying the sensitive self-assembly of nanostructures on miscut substrates. 21,41 Next, we analyze the measurement of the wetting layers as a function of miscut angles. From a thermodynamic point of view, transition from a flat film to undulated surface occurs because elastic energy relaxation eventually overcomes the extra cost of creating an undulated surface during growth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, current researches mainly focus on the improvement of luminescence properties by acquiring quantum dots with high density, uniform sizes and other special structures. Zhou et al 71 observed a quite strong Photoluminescence (PL) peak of dense GeQDs on a miss-cut substrate even at 300 K, as shown in Fig. 9, which was attributed to the good con¯nement of excitons in dense GeQDs due to the absence of the wetting layer.…”
Section: Preparation and Structures Of Geqds On Planar Substratementioning
confidence: 95%
“…The mechanism behind the formation and stability of these nanowires are attributed to abnormal faceting of the wetting layer [6, 13] or extended huts [10, 20], which is driven by the low surface energy of their {1 0 5} side facets under equilibrium phase. These lateral nanowires have shown potential applications for nano-electronics [10, 21], spintronic devices [22, 23], and optoelectronics [24, 25]. …”
Section: Introductionmentioning
confidence: 99%